The quality of a woman's diet is associated with household food insecurity in rural in Nepal (PoSHAN). - Klemm, Rolf. (Tufts University. Tisch Library., 2016)
Dr. Klemm examines the nutritional vunerability of women in the Nepali society along with factors such as family wealth, education, and seasons.; Nutrition School: NIL Symposium Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy